Cold consolidation and coercivity enhancement in Sm2Fe17N3 magnets by high-pressure torsion. (15th March 2023) - Hosokawa, Akihide; Hirayama, Yusuke
Abstract: Sm2 Fe17 N3 coarse powder was directly consolidated into a disc magnet by the high-pressure torsion technique. The huge superimposed hydrostatic pressure (10 GPa) made it possible to apply a large amount of plastic deformation to the disc as well as the powder particles of the brittle Sm2 Fe17 N3 compound at room temperature. This large deformation brought about grain subdivision inside powder particles and enabled to produce a bulk magnet having the coercivity of 5.7 kOe from the coarse powder having the coercivity of 1 kOe without reducing the particle size. It was clarified that those grain subdivision events are accompanied by the motion of dislocations confined in non-basal planes. Synchrotron X-ray diffractometry was also performed and revealed that too large strain, however, results in the disappearance of the hard magnetic Sm2 Fe17 N3 phase and the eventual loss of the coercivity. Graphical abstract: Image, graphical abstract